Strategy for Developing Human Resource Competencies Based on Data Analytics to Enhance Organizational Productivity and Economic Competitiveness - Hadikusumo, Reina A. (Asian Journal of Multidisciplinary Research, 2025)
This study analyzes data analytics-based human resource (HR) competency development strategies to improve organizational productivity and economic competitiveness in the digital age, using a qualitative library research approach from journals indexed by Google Scholar, Scopus, and national publications from 2020 to 2026. The background highlights the crucial role of data analytics in identifying skill gaps such as digital literacy and data analysis, with case studies showing a 95% correlation between digitization and a 90% increase in competency, despite adaptation challenges in Indonesia causing stagnant productivity and competitive lag. The problem formulation covers four aspects: (1) mapping competency gaps through analytical dashboards and HRIS with 98% accuracy; (2) effective strategies such as AI-driven upskilling, gamified e-learning, and predictive reskilling that increase productivity by 20-42%; (3) significant contribution to competitiveness (β=0.32-0.45, p<0.05) via product differentiation and operational efficiency of 30-50%; and (4) major obstacles in the form of data fragmentation (70% of Deloitte cases), lack of data literacy, and cultural resistance. Thematic-narrative synthesis analysis confirms that people analytics minimizes subjectivity, optimizes training ROI, and positions Indonesian organizations to be globally competitive through technology-transformational leadership synergy. Solutions include phased data literacy training, cloud-based HRIS, and change management for up to 40% effectiveness. The findings recommend gradual adoption for HR practitioners for sustainable transformation in Industry 5.0, with limitations due to reliance on current literature.